Study on the role of ethnic koreans in Кazakhstan: focusing on the assembly of people of Кazakhstan - Min, Сhu Young (Public Administration and Civil Service, 2018)
Ethnic Koreans in Kazakhstan have a positive image and have been mentioned as a main minority group in Kazakhstan. In this regard, this paper tried to find the reason that how they have been successfully integrated into the Kazakhstani society. To find the answer, the article explores the role of ethnic Koreans from Soviet times to independent Kazakhstan. As a result, the two factors might make the result of their stable settlement. First factor is the Koreans’ special adaptation ability and friendly characteristics, passed down from soviet Koreans. The second is tolerant and gradual national policies of Kazakhstan and its specialized mechanism-APK.